Varying Weed Densities Alter the Corn Transcriptome, Highlighting a Core Set of Weed‐Induced Genes and Processes with Potential for Manipulating Weed Tolerance. Issue 3 (1st November 2019) - Horvath, David P.; Clay, Sharon A.; Bruggeman, Stephanie A.; Anderson, James V.; Chao, Wun S.; Yeater, Kathleen
Abstract : Core Ideas: Corn increases the number of differentially expressed genes and the intensity of differential gene expression in response to increasing weed density. Genes associated with kinase signaling and transport functions are upregulated by weeds. Genes associated with protein production are downregulated by weeds. A sugar transporter ( PMT5 ) and NUCLEOREDOXIN 1 are upregulated by weeds under diverse conditions. The phenological responses of corn ( Zea mays L.) to competition with increasing densities of winter canola ( Brassica napus L.) as the weedy competitor were investigated. Changes in the corn transcriptome resulting from varying weed densities were used to identify genes and processes responsive to competition under controlled conditions where light, nutrients, and water were not limited. Increasing densities of weeds resulted in decreased corn growth and development and increased the number and expression intensity of competition‐responsive genes. The physiological processes identified in corn that were consistently induced by competition with weeds included protein synthesis and various transport functions. Likewise, numerous genes involved in these processes, as well as several genes implicated in phytochrome signaling and defense responses, were noted as differentially expressed. The results obtained in this study, conducted under controlled (greenhouse) conditions, were compared with a previously published study where the response of corn to competition with other species was evaluated under field conditions. Approximately one‐third of the genes were differentially expressed in response to competition under both field and controlled conditions. These competition‐responsive genes represent a resource for investigating the signaling processes by which corn recognizes and responds to competition. These results also highlight specific physiological processes that might be targets for mitigating the response of crops to weeds or other competitive plants under field conditions.